Criteria for risk evaluation in groundwater management projects: a comparative study - Miracapillo, Cinzia, author; Colorado State University, publisher (Colorado State University. Libraries, 2003)
Environmental protection criteria in the decision making process on the choice of a drainage system at a construction site in the city of Basel are presented here. A comparative quantitative evaluation between two drainage systems was possible focusing on the definition of equivalence criteria for aquifer protection and on the design of measures that guarantee the same safety level with respect to the above-mentioned criteria. The criteria discussed in this article are based on the hydraulic characteristics of the groundwater system, as they result from two-dimensional groundwater simulations in the area of the project.
Hydrology days 2003
AGU hydrology days 2003
23rd annual AGU hydrology days was held on March 31 - April 2, 2003 at Colorado State University.